Mō̜radok Thai mō̜radok tham - Phrakhrubhãvanãbodhikun ([Phrakhrū Phāwanāphōthikhun], 2010)
On ancient merit-making traditions for each of the twelve lunar months and the fourteen ancient customs of Northeastern Thailand, and on the stories of last 10 lives or the last ten re-births of Gautama Buddha as described in Theravada Buddhism.